Correction: Heterologous gene expression system for the production of hydrolyzable tannin intermediates in herbaceous model plants - Chihiro Oda-Yamamizo; Nobutaka Mitsuda; Carsten Milkowski; Hideyuki Ito; Kentaro Ezura; Ko Tahara (Journal of Plant Research, 2023)

Heterologous gene expression system for the production of hydrolyzable tannin intermediates in herbaceous model plants - Chihiro Oda-Yamamizo; Nobutaka Mitsuda; Carsten Milkowski; Hideyuki Ito; Kentaro Ezura; Ko Tahara (Journal of Plant Research, 2023)
Aluminum toxicity is the main factor limiting the elongation of plant roots in acidic soil. The tree species Eucalyptus camaldulensis is considerably more resistant to aluminum than herbaceous model plants and crops. Hydrolyzable tannins (HTs) accumulating in E. camaldulensis roots can bind and detoxify the aluminum taken up by the roots. However, in herbaceous model plants, HTs do not accumulate and the genes involved in the HT biosynthetic pathway are largely unknown. The aim of this study was to establish a method for reconstituting the HT biosynthetic pathway in the HT non-accumulating model plant Nicotiana benthamiana . Four E. camaldulensis enzymes were transiently expressed in N. benthamiana leaves via Agrobacterium tumefaciens -mediated transformation. These enzymes included dehydroquinate dehydratase/shikimate dehydrogenases (EcDQD/SDH2 and EcDQD/SDH3), which catalyze the synthesis of gallic acid, the first intermediate of the HT biosynthetic pathway that branches off from the shikimate pathway. The others were UDP-glycosyltransferases (UGT84A25 and UGT84A26), which catalyze the conversion of gallic acid to β-glucogallin, the second intermediate. The co-expression of the EcDQD/SDHs in transgenic N. benthamiana leaf regions promoted the synthesis of gallic acid . Moreover, the co-expression of the UGT84As in addition to the EcDQD/SDHs resulted in the biosynthesis of β-glucogallin, the universal metabolic precursor of HTs. Thus, we successfully reconstituted a portion of the HT biosynthetic pathway in HT non-accumulating N. benthamiana plants. This heterologous gene expression system will be useful for co-expressing candidate genes involved in downstream reactions in the HT biosynthetic pathway and for clarifying their in planta functions.

Dehydroquinate dehydratase/shikimate dehydrogenases involved in gallate biosynthesis of the aluminum-tolerant tree species Eucalyptus camaldulensis - Ko Tahara; Mitsuru Nishiguchi; Evelyn Funke; Shin-Ichi Miyazawa; Takafumi Miyama; Carsten Milkowski (Planta, 2021)
Main conclusion Eucalyptus camaldulensis EcDQD/SDH2 and 3 combine gallate formation, dehydroquinate dehydratase, and shikimate dehydrogenase activities. They are candidates for providing the essential gallate for the biosynthesis of the aluminum-detoxifying metabolite oenothein B. Abstract The tree species Eucalyptus camaldulensis shows exceptionally high tolerance against aluminum, a widespread toxic metal in acidic soils. In the roots of E. camaldulensis , aluminum is detoxified via the complexation with oenothein B, a hydrolyzable tannin. In our approach to elucidate the biosynthesis of oenothein B, we here report on the identification of E. camaldulensis enzymes that catalyze the formation of gallate, which is the phenolic constituent of hydrolyzable tannins. By systematical screening of E. camaldulensis dehydroquinate dehydratase/shikimate dehydrogenases (EcDQD/SDHs), we found two enzymes, EcDQD/SDH2 and 3, catalyzing the NADP + -dependent oxidation of 3-dehydroshikimate to produce gallate. Based on extensive in vitro assays using recombinant EcDQD/SDH2 and 3 enzymes, we present for the first time a detailed characterization of the enzymatic gallate formation activity, including the cofactor preferences, pH optima, and kinetic constants. Sequence analyses and structure modeling suggest the gallate formation activity of EcDQD/SDHs is based on the reorientation of 3-dehydroshikimate in the catalytic center, which facilitates the proton abstraction from the C5 position. Additionally, EcDQD/SDH2 and 3 maintain DQD and SDH activities, resulting in a 3-dehydroshikimate supply for gallate formation. In E. camaldulensis , EcDQD/SDH2 and 3 are co-expressed with UGT84A25a/b and UGT84A26a/b involved in hydrolyzable tannin biosynthesis. We further identified EcDQD/SDH1 as a “classical” bifunctional plant shikimate pathway enzyme and EcDQD/SDH4a/b as functional quinate dehydrogenases of the NAD + /NADH-dependent clade. Our data indicate that in E. camaldulensis the enzymes EcDQD/SDH2 and 3 provide the essential gallate for the biosynthesis of the aluminum-detoxifying metabolite oenothein B.

Sinapate esters in brassicaceous plants: biochemistry, molecular biology, evolution and metabolic engineering - Carsten Milkowski; Dieter Strack (Planta, 2010)

Genomic microstructure and differential expression of the genes encoding UDP-glucose:sinapate glucosyltransferase (UGT84A9) in oilseed rape (Brassica napus) - Juliane Mittasch; Sabine Mikolajewski; Frank Breuer; Dieter Strack; Carsten Milkowski (Theoretical and Applied Genetics, 2010)

The role of UDP-glucose:hydroxycinnamate glucosyltransferases in phenylpropanoid metabolism and the response to UV-B radiation in Arabidopsis thaliana - Dirk Meißner; Andreas Albert; Christoph Böttcher; Dieter Strack; Carsten Milkowski (Planta, 2008)

The genes BnSCT1 and BnSCT2 from Brassica napus encoding the final enzyme of sinapine biosynthesis: molecular characterization and suppression - Diana Weier; Juliane Mittasch; Dieter Strack; Carsten Milkowski (Planta, 2007)

Secondary product glycosyltransferases in seeds of Brassica napus - Juliane Mittasch; Dieter Strack; Carsten Milkowski (Planta, 2006)

Resveratrol glucoside (Piceid) synthesis in seeds of transgenic oilseed rape (Brassica napus L.) - Alexandra Hüsken; Alfred Baumert; Carsten Milkowski; Heiko C. Becker; Dieter Strack; Christian Möllers (Theoretical and Applied Genetics, 2005)

Cloning and heterologous expression of a rape cDNA encoding UDP-glucose:sinapate glucosyltransferase - Carsten Milkowski; Alfred Baumert; Dieter Strack (Planta, 2000)

A DNA Fragment from the Cyanobacterium Synechocystis sp. PCC 6803 Mediates Gene Expression Inducible by Osmotic Stress in E. coli - Carsten Milkowski *, , Ariel Quinone; Martin Hagemann (Current Microbiology, 1998)